AKTIVITAS ANTIOKSIDAN RAMUAN TRADISIONAL MADURA â€œSUBUR KANDUNGANâ€ - Resmisari, Ruri Siti (El-Hayah : Jurnal Biologi, 2014)
Traditional medicine "Subur Kandungan" is a medicine that is widely used and produced in Madura. The problem to develop Madura’s herb is raw material that hasn’t the standardized medicine used for Madura’s traditional medicine, because that raw materials are mostly purchased from traditional markets. This led to the standardization of Madura’s traditional medicine is difficult to do. This condition causes didn’t known active compounds contained in the Madura’s medicine. This study was conducted to determine the content of phytochemical compounds from ethanol extract medicine "Subur Kandungan" as well as antioxidant activity. Based on the results, it was concluded that the class of chemical compounds contained in the Madura’s traditional medicine "Subur Kandungan" are classified as a flavonoids and alkaloids, while the antioxidant activity of extracts of the medicine " Subur Kandungan " are expressed in IC50 was at 90.19 ppm classified as a strong antioxidant.